Health Care Provider Experiences With a Centralized Referral Network for Later Second-Trimester Abortions: The Case of Massachusetts [263]. (May 2015) - Ho, Stephanie; Janiak, Elizabeth
Abstract : INTRODUCTION: Socially vulnerable women are more likely to present for induced abortion in the later second trimester, and many report socioeconomic and interpersonal barriers that may delay care. The Access Program is a statewide, centralized referral network for women seeking 19+-week abortion services. The Program assists in providing pregnancy options counseling, individual scheduling of abortion care, triaging of preprocedure medical and social needs, and financial assistance. We performed a mixed-methods study to evaluate the acceptability, effect, and lessons learned from this unique program. METHODS: Thirty-three physicians, nurses, and staff working in hospitals accepting referrals from the Access Program were included in initial recruitment. Participation included completing a web-based survey, undergoing a semistructured qualitative interview, or both. We used inductive coding methods to analyze interview data. RESULTS: We received 16 completed surveys and conducted seven interviews. Common themes were identified using data from both methods. Health care providers expressed that the Program improved accessibility for patients and reduced the amount of office time spent on logistic factors. Patients referred through the Access Program were described as more socially and financially complex. Assistance with patient education, transportation, finances, and accommodations were identified as particularly helpful services. The utility of health care providers being able to hand off patients to the Access Program for services was also highlighted. Overall, respondents reported high satisfaction with the Program. CONCLUSION: The Access Program is highly acceptable to health care providers and positively affects patient care for a socioeconomically complex population. Implementing similar programs may help ameliorate barriers to care for vulnerable women in other states.